1990
DOI: 10.1007/bf03350681
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-pituitary-testicular function in 70 patients with myotonic dystrophy

Abstract: Hypothalamic-pituitary-testicular function was studied in 70 patients with myotonic dystrophy (MD). The diagnosis was confirmed by electromyography. The mean age of the patients was 36.2 +/- 13.2 yr and the duration of the disease was 11.17 +/- 8.01 yr. Testicular atrophy (testes less than or equal to 12 ml on a Prader orchidometer) was present in 65.5% of patients. Fertility among married patients was 66.6%. Mean testosterone plasma levels were 438 +/- 298 ng/dl vs 520 +/- 185 ng/dl in the control group (P = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 11 publications
0
25
0
1
Order By: Relevance
“…Indeed, many studies found hypogonadism with sperm count defects (Hortas et al, 2000), testicular atrophy in 65.5% of patients (Vazquez et al, 1990) and damage to the seminiferous tubules as evident on biopsy specimens (Takeda and Ueda, 1977). In women, the correlation between fertility and MD remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, many studies found hypogonadism with sperm count defects (Hortas et al, 2000), testicular atrophy in 65.5% of patients (Vazquez et al, 1990) and damage to the seminiferous tubules as evident on biopsy specimens (Takeda and Ueda, 1977). In women, the correlation between fertility and MD remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hypogonadism is frequently described and MD is associated with decreased fertility. Indeed, in men, MD may cause testicular atrophy and oligozoospermia due to tubular lesions (Vazquez et al, 1990). Yet, in women, the relationship between MD and infertility remains unclear and publications on the subject are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the literature, in which testicular atrophy is reported to be the most prominent feature in approximately 80% of DM1 patients, we routinely observed both testicular hypotrophy and oligozoospermia in our DM1 patients (data not shown). Histological studies have confirmed that the testicles of DM1 patients are characterized by an increase in the number and size of Leydig cells, as well as by tubular atrophy, hyalinization, and fibrosis of the seminiferous tubules and reduced spermatogenesis [3,19]. These structural gonadic changes correlate with endocrine findings [3,19,20], which point to markedly increased FSH levels, moderately increased or normal LH levels and moderately reduced T levels in male patients [21].…”
Section: Discussionmentioning
confidence: 75%
“…Primary hypogonadism, which occurs in approximately 80 % of young to middle-aged males, may not be evident till adulthood. Most of these men have isolated impairment of sperm production or function and atrophy with hyalinisation and fibrosis of the seminiferous tubules is observed on testicular biopsy [2]. Moreover, capacitation and acrosome reaction in the spermatozoa may be defective and may account for infertility in MD patients with relatively higher sperm counts [3].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated FSH levels alter estradiol-to-testosterone ratio and may cause gynaecomastia. Several studies have reported oligospermia and azoospermia in patients with myotonic dystrophy type 1 [2]. An association of larger CTG repeat alleles (in DMPK gene) with idiopathic azoospermia has been variably observed [4].…”
Section: Discussionmentioning
confidence: 99%